Risk Factors Proximate to Suicide and Suicide Risk Assessment in the Context of Denied Suicide Ideation. Issue 3 (21st April 2017) - Berman, Alan L.
Abstract : Health care providers have significant opportunities to identify individuals at near‐term risk for suicide, but lack empirical data on near‐term risk factors. This study aimed to identify dynamic, state‐related risk factors observed by clinical practitioners within the last 30 days of life of 157 patients who died by suicide and to compare these near‐term risk factors among patients who denied versus responded positively to having suicide ideation (SI) when last asked by a clinical practitioner prior to their death. Risk factors charted for the majority of all decedents were a history of prior suicide ideation and/or suicide attempt, current anxiety/agitation and sleep problems, current interpersonal problems or job/financial strain, current comorbid diagnoses, current social isolation/withdrawal, and a family history of mental disorder. Two‐thirds of patients denied having SI when last asked and one‐half of these patients were dead by suicide within 2 days. Decedents who denied having SI were quite similar in charted diagnoses, symptoms, behaviors, and environmental circumstances to decedents who responded affirmatively to having SI. Reliance on verbalized or reported SI as a gateway to a suicide risk assessment is questioned and the need for better understanding near‐term risk for suicide, particularly in the absence of stated SI, is highlighted.